Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Badan Usaha - Putra Agus Setiono, Revian Pradana (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2021)
This study aims to examine the factors that affect the compliance of corporate taxpayers who make tax payments. This study focuses on corporate taxpayers. The independent variables used in this study are Tax Knowledge, Tax Awareness and Tax Sanctions, while the dependent variable in this study is Taxpayer Compliance. The sample used in this study is an individual taxpayer who conducts business activities in the Surabaya area. The method used in this research is purposive sampling method. Respondents obtained in this study were 40 respondents who met the criteria and filled out the questionnaire correctly. Questionnaires are used in measuring validity and reliability testing to measure whether a questionnaire is valid and reliable. Then the data analysis technique used is descriptive statistical analysis, classical assumption test of multicollinearity test, autocorrelation test, heteroscedasticity test, and normality test, as well as using multiple regression analysis, coefficient of determination, F test and t test. The results of this study are the variable knowledge of taxation and tax sanctions affect the compliance of individual taxpayers who carry out business activities. While the tax awareness variable has no effect on tax compliance. This shows that although respondents are obedient in paying taxes, respondents still have a low level of awareness.